Adsorption Isotherm of Chromium (VI) into Zncl2 Impregnated Activated Carbon Derived by Jatropha Curcas Seed Hull - Mohammad, Masita; Ibrahim, Yakub; Zahira, Yaakob; Nilofar, Asim; Kamaruzzaman, Sopian (Institute of Physics Publishing, 2018)
Hexavalent chromium is carcinogenic and should be removed from industrial wastewater before discharged into water resources. Adsorption by using activated carbon from biomass is an economic and conventional way on removing the heavy metal ions from wastewater. In this research, activated carbon is synthesized from Jatropha curcas L. seed hull through chemical activation with ZnCl2 and carbonized at 800 °C (JAC/ZnCl2). The activated carbon has been characterized using FTIR, SEM-EDX, BET and CHNS-O analyzer. Adsorption isotherms have been analysed using Langmuir and Freundlich models to determine its removal mechanism. The maximum adsorption capacity of Cr (VI) metal ions onto JAC/ZnCl2 activated carbon is 25.189 mg/g and following Langmuir isotherm model which is monolayer adsorption.